2022
DOI: 10.48550/arxiv.2203.09051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Emergence of Bulges and Disks in the Universe

Abstract: This thesis makes use of the imaging data from the Advanced Camera for Surveys (ACS) of the Hubble Space Telescope (HST) in the Cosmic Evolution Survey (COSMOS) and the Deep Extragalactic VIsible Legacy Survey (DEV-ILS) field. We provide visual morphological classifications of 44,000 galaxies out to redshift z = 1 and above a stellar mass of 10 9.5 M (D10/ACS sample). We perform a robust Bayesian bulge-disk decomposition analysis of the D10/ACS sample. This study forms one of the largest morphological classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 314 publications
(704 reference statements)
0
1
0
Order By: Relevance
“…The variation in the morphology of bulges with wavelength provides an interpretation of the inconsistency between observations of high-redshift galaxies and modeling of galaxy evolution. It has been reported that bulges are predicted to have been formed at the redshift z ∼ 2, but galaxies at z = 1-3 are found to be mainly dominated by disks (van Dokkum et al 2013;Bruce et al 2014;Shibuya et al 2015;Toft et al 2017;Dimauro et al 2019;Tacchella et al 2019;Hashemizadeh 2022). In practical terms, for high-redshift galaxies, optical telescopes observe their rest-frame UV appearances.…”
Section: Multiwavelength Featuresmentioning
confidence: 99%
“…The variation in the morphology of bulges with wavelength provides an interpretation of the inconsistency between observations of high-redshift galaxies and modeling of galaxy evolution. It has been reported that bulges are predicted to have been formed at the redshift z ∼ 2, but galaxies at z = 1-3 are found to be mainly dominated by disks (van Dokkum et al 2013;Bruce et al 2014;Shibuya et al 2015;Toft et al 2017;Dimauro et al 2019;Tacchella et al 2019;Hashemizadeh 2022). In practical terms, for high-redshift galaxies, optical telescopes observe their rest-frame UV appearances.…”
Section: Multiwavelength Featuresmentioning
confidence: 99%